Optimizing the Dyeing of Silk Fabric with Gemstone Powder using Exhaustion Process - Nitayaphat, Walaikorn; Jintakosol, Thanut (Asian Journal of Chemistry, 2020)
The silk fabrics were modified by a cationic reagent, N-(3-chloro-2-hydroxypropyl)trimethylammonium chloride in order to prepare the fiber to be dyed with gemstone powder (i.e. malachite, lapis lazuli and jasper) by an exhaustion process. The effect of dyeing conditions such as temperature, dyeing time, pH and gemstone powder concentration on colour strength were investigated. Optimum results were achieved when dyeing at a liquor ratio of 1:100 at pH 3 (for malachite and jasper) or pH 5 (for lapis lazuli), at 90 ºC for 60 min. The color fastness to crocking of cationic treated silk fabric dyed with gemstone powder was fair to good, whereas the color fastness to washing was poor to fair. However, the colour fastness to light was very good. This study demonstrated that cationic treated silk fabric can dyed with gemstone powder by exhaustion process.